Effect of Arginine on Microwave-Induced Pre-gelation of Sturgeon Myofibrillar Protein under Low Salt Condition - SHI Tong, XIE Yu, ZHANG Hao, WANG Xin, LI Mengzhe, GAO Ruichang (Shipin Kexue)
In order to investigate the effect of arginine (Arg) on the microwave-induced pre-gelation of myofibrillar protein (MP) from sturgeon under low salt condition, MP added with different concentrations of Arg was microwaved and evaluated for physicochemical, structural and morphological properties and intermolecular interactions after 1, 3 and 5 min (< 40 ℃). It was found that the solubility of MP decreased with increasing microwaving time and was improved by appropriate concentrations of Arg (P < 0.05). The turbidity of MP microwaved for 5 min significantly decreased with increasing addition of Arg (P < 0.05). The particle size decreased with increasing levels of Arg addition. In addition, Arg inhibited the formation of large protein clusters during microwave heating as shown by atomic force microscopy. In the control group, the contents of ionic and hydrogen bonds decreased significantly after microwave treatment for 3 min, while the contents of hydrophobic interaction and disulfide bond increased significantly (P < 0.05). The addition of 40 mmol/L Arg inhibited the ionic bond and hydrophobic interaction and increased the hydrogen and disulfide bonds. The molecular dynamics simulation results showed that at 300 K, the root mean square deviation (RMSD) for myosin increased from about 0.52 to 5.85 nm after Arg binding to it, and the radius of gyration (Rg) also increased, indicating that Arg promoted the dissociation of MP aggregates under low salt condition, and the aggregate characteristics changed from larger protein clusters to smaller particles. Furthermore, binding of Arg to myosin decreased its structural tightness, resulting in more loose protein conformation. The findings of this study provide sufficient conditions for enhancing protein cross-linking in the gel strengthening stage.